Extracellular matrix-based cancer targeting. Issue 10 (October 2021) - Karamanos, Nikos K.; Piperigkou, Zoi; Passi, Alberto; Götte, Martin; Rousselle, Patricia; Vlodavsky, Israel
Abstract : Tumor extracellular matrix (ECM) operates in a coordinated mode with cancer and stroma cells to evoke the multistep process of metastatic potential. The remodeled tumor-associated matrix provides a point for direct or complementary therapeutic targeting. Here, we cover and critically address the importance of ECM networks and their macromolecules in cancer. We focus on the roles of key structural and functional ECM components, and their degradation enzymes and extracellular vesicles, aiming at improving our understanding of the mechanisms contributing to tumor initiation, growth, and dissemination, and discuss potential new approaches for ECM-based therapeutic targeting and diagnosis. Highlights: Modified extracellular matrix in the tumor microenvironment dictates cancer cell properties, metastatic potential, and formation of premetastatic niches. Proteoglycans and hyaluronan in provisional matrix modulate the bioavailability of matrix-bound effectors, cancer cell signaling, angiogenesis, and tumor spread. The outside-in interactions of integrins with tumor matrix, the migratory tracks for cancer cells created by fibrillar collagen fiber alignment, and the intense trafficking of extracellular vesicles, impact tumor progression. Proteolytic (matrix metalloproteinases and cathepsins) and glycosidic (heparanase and hyaluronidases) enzymes mediate protumorigenic interactions and stemness, associated with therapeutic resistance. Heparanase promotes the aggressive phenotype of cancer, while heparanase-2 functions as a tumor suppressor. Interference with exosome biogenesis, miRNAs functions, provisional matrix and premetastatic niche formation, may drive future cancer therapeutics.